Assessment of environmental impacts of cage aquaculture on Lake Volta of Ghana - Karikari, Anthony Yaw (KNUST, 2025)
A thesis submitted to the Department of Fisheries and Watershed Management in partial fulfillment of the requirements for the award of the degree of Doctor of Philosophy (Ph.D) in Aquaculture and Environment